A systematic review of quantitative observational studies investigating psychological distress in testicular cancer survivors. Issue 4 (11th January 2018) - Smith, Allan "Ben"; Rutherford, Claudia; Butow, Phyllis; Olver, Ian; Luckett, Tim; Grimison, Peter; Toner, Guy; Stockler, Martin; King, Madeleine
Abstract: Objective: Testicular cancer (TC) affects young men and may cause psychological distress despite a good prognosis. This systematic review evaluated the prevalence, severity, and correlates of anxiety, depression, fear of cancer recurrence (FCR), and distress in TC survivors. Methods: A systematic search of literature published 1977 to 2017 was conducted to find quantitative studies including TC survivor–reported outcomes relevant to review objectives. The quality of included articles was assessed, and a narrative synthesis conducted. Results: Of 6717 articles identified, 66 (39 good, 20 fair, and 7 poor quality) reporting results from 36 studies were included. Testicular cancer survivors' mean anxiety levels were higher than in the general population, while mean depression and distress were no different. Clinically significant anxiety (≈1 in 5) and to a lesser extent distress (≈1 in 7), but not depression, were more prevalent in TC survivors than the general population. Approximately 1 in 3 TC survivors experienced elevated FCR. Poorer psychological outcomes were more common among TC survivors who were single, unemployed/low socio‐economic status, suffering from co‐morbidities, experiencing worse symptoms/side effects, and using passive coping strategies. Conclusions: Many TC survivors do not experience significant psychological morbidity, but anxiety and FCR are prevalent. Inadequate coping resources (eg, low socio‐economic status and social support) and strategies (eg, avoidance) and greater symptoms/side effects were associated with poorer outcomes. Theoretically driven prospective studies would aid understanding of how outcomes change over time and how to screen for risk. Age and gender appropriate interventions that prevent and manage issues specific to TC survivors are also needed.